Optimalisasi Transaksi Keuangan Digital melalui Pelatihan Penggunaan Financial Payment Gateway bagi Mitra Kelompok Usaha Mikro - Besse Wediawati; rike setiawati; Zulfina Adriani; RTS Ratnawati; Iskandar Syam (Journal Of Rural Community Development, 2024)
Abadi Group is a Micro Business group in the pineapple processing industry located in Sentra Nanas Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency. This group has limited use of digital financial applications, which hinders the smooth running of their business payment transactions. This activity aims to help solve partner problems by facilitating training to improve digital financial literacy, especially in terms of financial payment gateways through the QRIS (Quick Response Code Indonesian Standard) application. The Abadi business group consists of 15 people. This activity uses the participant learning center method including direct instruction, simulation and direct practice. The training activities were carried out at the Abadi Group secretariat in Parit IV, Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency. Training materials include Digital Financial Literacy; Financial Payment Gateway, Registration and use of QRIS in transactions. The results of this activity, Abadi group partners successfully registered their businesses so that they had QRIS merchants. Partners can also use the QRIS application in their business payment transactions, thereby reducing dependence on cash and reaching wider consumers who prefer online transactions. Furthermore, it allows micro-business partners to have automatic transaction recording so that they can help monitor cash flow and manage their finances better.